Life and death in a submarine volcanic ash dune: the case of a group of patagonian miocene echinoids - Palópolo, Evangelina Elizabeth (2019)
Fil: Palópolo, Evangelina. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro. Argentina.